Dimensão ética do gerenciamento em enfermagem - Lara, Silvéria Rosa [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
In managing an Inpatient unit, nurses face the need to make decisions involving agents in the institution’s internal and external environments, and all these measures are influential, regardless of how beneficial they may be. Hence, ethical issues constitute an important dimension of nursing management. This study aimed at identifying measures and/or interventions adopted by managing nurses at Inpatient Units in the Botucatu School of Medicine University Hospital - UNESP with the purpose to analyze professional ethics. The study involved nurses holding technicalsupervision positions in sectors related to the Nursing Division, comprising a total number of 20. The exploratory method was used by means of taped interviews with a qualitative approach based on the Collective Subject Discourse. Human resources deficit was observed as nurses’ major concern in relation to nursing care provision. The managers seek the nursing staff’s development by means of educational activities in their own unit at the same time that they adopt those offered by the hospital. When ethical violations occur, they resort to measures ranging from individual strategies for violators’ orientation to legal intervention. The resolution of ethical conflicts by nursing managers generally occurs in a gradual fashion by taking into account their compromising level, whether in relation to the patient or to the multiprofessional team. Educational activities are focused on the development of technical skills aiming at preventing physical damage to patients although educational activities targeted at the development of professionals’ ethical awareness were not mentioned

No gerenciamento de Unidade de Internação o enfermeiro se depara com a necessidade de tomada de decisões que envolvem os agentes dos ambientes interno e externo da instituição e todas essas medidas carregam consigo um poder de influenciar, independendo do seu grau de benefício. Logo, as questões éticas constituem dimensão importante da administração de enfermagem. O objetivo deste trabalho foi identificar medidas e/ou intervenções adotadas por enfermeiros gerentes de Unidades de Internação do Hospital das Clínicas da Faculdade de Medicina de Botucatu - UNESP, visando à observância da ética profissional. O estudo envolveu enfermeiros que ocupam cargos de supervisão técnica nas seções ligadas à Divisão de Enfermagem, em número de 20. O método foi exploratório, por meio de entrevistas gravadas, com abordagem qualitativa, tendo como referencial o Discurso do Sujeito Coletivo. Evidenciou-se como maior preocupação dos enfermeiros, em relação à prestação da assistência de enfermagem, o déficit de recursos humanos. Os gestores buscam o desenvolvimento do pessoal de enfermagem por meio de atividades educativas na própria unidade e ao mesmo tempo adotam às que são oferecidas pelo hospital. Quando da ocorrência de infrações éticas, lançam mão desde estratégias individualizadas de orientação do infrator até busca de intervenção jurídica. A resolução de conflitos éticos pelos gestores de enfermagem geralmente acontece de forma gradual, considerando o nível de comprometimento, seja do paciente ou da equipe multiprofissional. As atividades educativas são focalizadas no desenvolvimento de habilidades técnicas visando prevenir danos físicos ao paciente, porém não foram mencionadas atividades educativas direcionadas ao desenvolvimento da consciência ética dos profissionais
Keywords: Etica da enfermagem